2021
DOI: 10.3390/cells10051176
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Functions of Polo-Like Kinases in Mice and Their Applications as Cancer Targets with a Special Focus on Ovarian Cancer

Abstract: Polo-like kinases (PLKs) belong to a five-membered family of highly conserved serine/threonine kinases (PLK1-5) that play differentiated and essential roles as key mitotic kinases and cell cycle regulators and with this in proliferation and cellular growth. Besides, evidence is accumulating for complex and vital non-mitotic functions of PLKs. Dysregulation of PLKs is widely associated with tumorigenesis and by this, PLKs have gained increasing significance as attractive targets in cancer with diagnostic, progn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 328 publications
(497 reference statements)
0
12
0
Order By: Relevance
“…We focused on PLK2 among the candidate proteins predicted to bind HSPB5 by MG132 treatment. PLK2 belongs to the “Polo” family of serine/threonine kinases and functions in mitosis and cell cycle regulation [ 24 ]. PLK2 showed a significant value of emPAI, as acquired by mass spectrometry, and emPAI increased with ER stress ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We focused on PLK2 among the candidate proteins predicted to bind HSPB5 by MG132 treatment. PLK2 belongs to the “Polo” family of serine/threonine kinases and functions in mitosis and cell cycle regulation [ 24 ]. PLK2 showed a significant value of emPAI, as acquired by mass spectrometry, and emPAI increased with ER stress ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we explored the binding proteins of HSPB5 and newly identified PLK2, which binds to HSPB5 under ER stress by MG132 treatment. PLK2 belongs to the polo-like kinase family and has recently been investigated as a therapeutic target for tumors [ 24 ]. We further showed that PLK2 phosphorylates serine 19, one of the three phosphorylation sites of HSPB5 [ 35 , 40 ], suppresses apoptosis induced by MG132-induced ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, PLK1 inhibitors act on multiple stages of cell mitosis, such as Annotation: R > 0:8: highly correlated; 0:5 < R < 0:8: moderate correlation; 0:3 < R < 0:5: low correlation; R < 0:3: irrelevant. 7 Disease Markers blocking centrosome maturation, spindle formation, and cytokinesis, thereby disrupting cell division and cycle progression and ultimately leading to tumor cell death [12]. Studies have shown that PLK1 is overexpressed in colorectal cancer [36], pancreatic cancer [37], gastric cancer [38], prostate cancer [39], thyroid cancer [40], bladder cancer, and other tumors [41], and the high expression of PLK1 indicates poor clinical prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Polo-like kinase 1 (PLK1), a member of the PLK family, is a serine/threonine protein kinase and is widely recognized as an oncogene. PLK1 plays a crucial role in the cell cycle and drives cell proliferation by promoting mitosis and cytokinesis [11][12][13]. In addition, PLK1 also has roles in meiosis, including regulating cancer cell invasiveness and preventing cancer cell apoptosis [14].…”
Section: Introductionmentioning
confidence: 99%
“…PLK1 (Polo-like kinase 1) is a member of the polo-like kinase family of serine/threonine protein kinases and plays an important role in regulating the cell cycle. PLK1 contains an N-terminal catalytic domain, C-terminal polo-box domain (PBD), and a phosphopeptide connecting region in the middle that connects both N- and C-terminal domains of the PLK1 [ 5 ]. The C-terminal PBD consists of two polo-box structures, an important feature of PLK family proteins, whereas the N-terminal catalytic domain of PLK1 is a Serine/Threonine kinase domain [ 6 ].…”
Section: Introductionmentioning
confidence: 99%